KONSEP PENDIDIKAN AKHLAK DALAM SIRAH NABAWIYAH KARYA SYAIKH SHAFIYYURRAHMAN AL-MUBARAKFURI DAN IMPLIKASINYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Irawati Indah; Firman Robiansyah; Darmawan Darmawan (Universitas Pendidikan Indonesia, 2021)
Moral education is the main foundation in preventing moral deviation, achieving the goal of life in a directed manner so that it becomes a superior person and has a noble morality. But today there are still many moral deviations committed by students ranging from low cases to criminality. The Prophet (pbuh) became an example in the cultivation of noble morals in each individual. Thus researchers are interested to analyze in depth about the concept of moral education of the Prophet Muhammad in the book sirah nabawiyah by Shaykh Shafiyyurrahman Al-Mubarakfuri. The research approach used is qualitative approach using literature study method. Data collection techniques in this study in the form of documentation studies, namely researchers read the book sirah nabawiyah by Shaykh Shafiyyurrahman Al-Mubarakfuri and trace other sources relevant to the topic of discuccion. The results showed that the book of sirah nabawiyah by Shaykh Shafiyyurrahman Al-Mubarakfuri contains the principles of moral education, including moral education in relation to Allah swt includes tawhid, love of God, repentance, piety, worship, patience, king’, tawadhu to Allah, gratitude, tawakal, pray to God, and dhikr. Moral education in relation to the Prophet(s) includes loving the Messenger, glorifying the Messenger, and obeying. Moral education in relation to oneself includes honesty, creativity, independence, discipline, responsibility, unyielding, and fondness for reading. Moral education in relation to others includes taawun, compassion and assertiveness, tasamuh, philanthropy, humble, forgiving, maintaining brotherhood, caring for others, cooperation, deliberation, and amar ma’ruf nahi munkar. As well as the methods used include conscientiousness, hanituation, advice, story, motivation and punishment. Based on the result of the analysis is expected to exemplify and be able to instill the noble morals of the Prophet(s) through the learning process of Islamic religious education in elementary school.Keywords: Moral Education, Sirah Nabawiyah, Islamic Education